Online Genome Analysis Resources for Educators, a Comparative ReviewReviews of: Carolina Biological Supply Company, www.carolina.com; Bio-Rad, www.bio-rad.com; Edvotek Inc., www.edvotek.com; Hiram Genomics Store, www.hiramgenomicsstore.com; and 23andMe, www.23andme.com. - Sarah Grace Prescott (American Society for Microbiology, 2012)
A comparative review of several companies that offer similar kits or services that allow students to isolate DNA (human and others), amplify it by PCR, and in some cases sequence the resulting sample. The companies include: Carolina® Biological Supply Company, Bio-Rad®, Edvotek® Inc., Hiram Genomics Store, and 23andMe.